2012
DOI: 10.1073/pnas.1201031109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of streptokinase gene expression improves survival after group A streptococcus infection in mice

Abstract: The widespread occurrence of antibiotic resistance among human pathogens is a major public health problem. Conventional antibiotics typically target bacterial killing or growth inhibition, resulting in strong selection for the development of antibiotic resistance. Alternative therapeutic approaches targeting microbial pathogenicity without inhibiting growth might minimize selection for resistant organisms. Compounds inhibiting gene expression of streptokinase (SK), a critical group A streptococcal (GAS) virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 51 publications
3
63
0
Order By: Relevance
“…Blocking the ability of GAS to acquire Ska-activated plasmin activity on its surface, either by genetic manipulation of Ska or by inhibition of plasmin activity with aprotinin, significantly reduced virulence in a murine infection model. Pharmacological inhibition of Ska in combination with other virulence determinants has recently been shown to reduce GAS virulence in mice (28). Our data have shown that inhibition of plasmin protease activity (the critical effector mechanism of Ska) is sufficient to reduce GAS virulence in a murine skin infection model.…”
Section: Discussionmentioning
confidence: 55%
“…Blocking the ability of GAS to acquire Ska-activated plasmin activity on its surface, either by genetic manipulation of Ska or by inhibition of plasmin activity with aprotinin, significantly reduced virulence in a murine infection model. Pharmacological inhibition of Ska in combination with other virulence determinants has recently been shown to reduce GAS virulence in mice (28). Our data have shown that inhibition of plasmin protease activity (the critical effector mechanism of Ska) is sufficient to reduce GAS virulence in a murine skin infection model.…”
Section: Discussionmentioning
confidence: 55%
“…Using this well-established model (59), mice were subcutaneously injected with GAS, given a day to establish an infection, and then intraperitoneally treated with compound daily for 5 days. Mice treated with CCG-2979 showed a statistically significant improvement in survival, while those treated with the CCG-102487 analog were not protected from GAS-induced mortality (7).…”
Section: Small Molecules That Affect Host-pathogen Interactionsmentioning
confidence: 99%
“…The effect of one chemical analog, CCG-102487, on global gene expression was examined by microarray analysis, which demonstrated that expression of 29% of GAS genes in addition to that of ska was altered, with the vast majority of them being reduced in expression. Included among these were other virulence-associated genes coding for adhesins and toxins, along with genes encoding some metabolic functions (7).…”
Section: Small Molecules That Affect Host-pathogen Interactionsmentioning
confidence: 99%
“…After screening more than 300 000 chemicals, Ginsburg and colleagues 5 identified a small set that specifically turned off streptokinase in the bacteria, several of which proved effective in protecting group A streptococci-sensitive mice from fatal infection.…”
Section: Blocking Bacterial Infectionmentioning
confidence: 99%